Investigation into the influence of Condition Based Maintenance on employee safety and site profitability relating to Safety Critical Sites - Watkinson, Jonathan (Cranfield University, 2025)
Safety Critical Manufacturing Sites within the United Kingdom are governed by the Control of Major Accidents and Hazards (COMAH). These sites have a specific challenge through needing to keep their ageing sites safe and compliant, whilst also needing to keep manufacturing costs low, in order to stay competitive in an ever-changing market. In order to meet the challenge of staying safe, and profitable, a Proactive Predictive Maintenance (PdM) Strategy is needed. This paper will investigate the potential Condition Based Maintenance (CBM) has in enhancing sites safety, and profitability, by reviewing academic papers and industrial practices through multiple case studies; highlighting the gaps and providing recommendations. The paper will include information from primary research, reviewing academic papers to ascertain from a white paper perspective what information is available. Similarly, it will then conduct secondary research via a technical questionnaire targeting industry to gather insights on practices and the challenges of using CBM. Additionally, it will use multiple case studies to underpin the primary and secondary research, finally summarising all through a conclusion section. Note. The work within this paper is drawn from academic research, industrial practices and from a specific case study. Any critical analysis and the thoughts relating to it are solely that of the author.
Keywords: COMAH; Condition Based Maintenance; Reliability; Acoustic Leak Detection; Motion Amplification; Predictive Maintenance